2019
DOI: 10.3390/pr7090576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrothermal Pretreatment on Volatile Fatty Acids Production from Source-Separated Organics

Abstract: The current study investigates the effect of hydrothermal pretreatment (HTP) on acidification of source-separated organics (SSO) in terms of volatile fatty acids (VFAs) production and solubilization. Temperature and retention time for HTP of SSO ranged from 150 to 240 • C and 5 to 30 min, respectively. The soluble substance after hydrothermal pretreatment initially increased, reaching its peak at 210 • C and then declined gradually. The highest overall chemical oxygen demand (COD) solubilization of 63% was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(52 reference statements)
2
9
0
Order By: Relevance
“…However, from around day 20, in line with the drop in H 2 level, acetate and lactate became the dominant acids in both reactors, but with differences in the total amounts depending on the initial inoculum. At this time, the pH reached 3.8 ± 0.1 in WW-F and 4.0 ± 0.2 in CO-F and total gas production was very low (<1 g C in gas /L substrate d in WW-F; <2 g C in gas /L substrate d in CO-F), in line with previous studies on hydrolysis of food waste [6,10,20,42,43]. In contrast, in the sludge reactors (CO-S and WW-S), methane content and pH did not drop to similarly low levels when operating at initial parameters of OLR 14.2 kg VS/m 3 /d and HRT 5 days.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, from around day 20, in line with the drop in H 2 level, acetate and lactate became the dominant acids in both reactors, but with differences in the total amounts depending on the initial inoculum. At this time, the pH reached 3.8 ± 0.1 in WW-F and 4.0 ± 0.2 in CO-F and total gas production was very low (<1 g C in gas /L substrate d in WW-F; <2 g C in gas /L substrate d in CO-F), in line with previous studies on hydrolysis of food waste [6,10,20,42,43]. In contrast, in the sludge reactors (CO-S and WW-S), methane content and pH did not drop to similarly low levels when operating at initial parameters of OLR 14.2 kg VS/m 3 /d and HRT 5 days.…”
Section: Resultssupporting
confidence: 90%
“…The effect of inoculum source in processing food waste for acid production has also been evaluated in previous studies, although mainly in batch mode. Those studies identified inoculum source as a detrimental factor for process performance [4,18,21,43], as also found in the present study. However, based on the Illumina sequencing results, the inoculum source appeared to have minor effects on the development of the microbial community structure.…”
Section: Importance Of Inoculum Sourcesupporting
confidence: 88%
See 1 more Smart Citation
“…The Special Issue showcases ten full-length original research articles [13][14][15][16][17][18][19][20][21][22], one short communication [23], and one review article [24] covering different aspects of various processes for bioenergy and resource recovery from biowaste. Specifically, the accepted manuscripts covered a range of essential topics in the areas of anaerobic digestion, microbial fermentation, and thermochemical conversion targeting various value-added resources, including biogas, syngas, bio-oil, and organic acids ( Figure 1).…”
Section: Statistics Of the Special Issuementioning
confidence: 99%
“…Notably, the application of strong base anionexchange resin could alleviate feedback inhibition of caproate, which can potentially provide a simple solution compared to other approaches previously reported in the literature, including electrodialysis. Kakar et al [20] investigated temperatures and retention times for the application of the thermal hydrolysis process as a feedstock pretreatment method for improving fermentative…”
Section: Overview Of the Contributionsmentioning
confidence: 99%